2020
DOI: 10.1037/cep0000236
|View full text |Cite
|
Sign up to set email alerts
|

Learning performance is influenced by the social environment in cichlid fishes.

Abstract: It has been hypothesised that some specialised cognitive abilities may have evolved because of the challenges of living in complex social environments. Therefore, more-social species might be able to learn faster than less-social species. The aim of this study was to develop a learning framework to test how more- and less-social Lamprologine cichlid fishes perform across associative learning tasks. These cichlids are a group of closely related species with similar ecologies and life histories but varying degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Zebrafish as well as other fish species have been found to acquire memory of CS–US association 11 13 , 16 , 17 , 22 , 40 , 48 , 49 . However, the studies in which such learning/memory performance was demonstrated with these fish species often required larger number of training trials and more subjects than employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zebrafish as well as other fish species have been found to acquire memory of CS–US association 11 13 , 16 , 17 , 22 , 40 , 48 , 49 . However, the studies in which such learning/memory performance was demonstrated with these fish species often required larger number of training trials and more subjects than employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, African cichlids have been studied for neophobia and learning performance 15 , and spatial learning has been demonstrated in other cichlid species 16 . The effect of social environment on learning has also been studied in cichlids 17 . Guppies have been used to test learning and memory and underlying neuroplastic changes in the brain 18 as well as for brain morphology correlates 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salena and Balshine (2020), Stanbrook, Jodoin, Culbert, Shultz, & Balshine (2020), and Berhane and Gazes (2020) test the relation between sociality and cognition. The former two papers take a comparative, among-species approach, while the latter examines variation among individual variation.…”
Section: Contributionsmentioning
confidence: 99%
“…The relationship between group size and brain size/neocortex size in anthropoid primates has since been replicated in several other studies (Dunbar, 1995; Barton, 1996; Walker et al ., 2006; Dunbar & Shultz, 2007), which inevitably led to the expansion of the SIH beyond primates. Since its inception, support for the SIH has been found in various species of mammals (Wang et al ., 2018; Johnson-Ulrich & Holekamp, 2020; Fox, Muthukrishna & Shultz, 2017; Sakai et al ., 2011; Dunbar & Bever, 1998; Borrego & Gaines, 2016), birds (Beauchamp & Fernández-Juricic, 2004; Kulahci et al ., 2016; Langley et al ., 2018 b ; Aplin et al ., 2012; Boogert, Farine & Spencer, 2014; Morand-Ferron & Quinn, 2011; Lipkind et al ., 2002; Ashton et al ., 2018 a ; Speechley et al ., 2024), fish (Fischer et al ., 2015; Triki et al ., 2019; Brandão, Braithwaite & Goncalves-de-Freitas, 2015; Stanbrook et al ., 2020; Leris & Reader, 2016; Ausas et al ., 2019), and invertebrates (Liedtke & Schneider, 2017; Kamhi et al ., 2016; Ott & Rogers, 2010; Amador-Vargas et al ., 2015; Seid & Junge, 2016). However, support for the SIH has not been consistent among or within taxa (Templeton, Kamil & Balda, 1999; Iwaniuk & Arnold, 2004; Kverková et al ., 2018; Forss et al ., 2016; DeCasien et al ., 2017; Fedorova, Evans & Byrne, 2017), with many papers reporting conflicting results, even within the same species, depending on the metric of sociality or cognition used (Fox et al ., 2017; Kamhi et al ., 2016; Sakai et al ., 2016; Reader, Hager & Laland, 2011; DeCasien & Higham, 2019).…”
Section: Introductionmentioning
confidence: 99%